Uncovering the Roles of Clocks and Neural Transmission in the Resilience of Drosophila Circadian Network - Jaumouillé, Edouard; Koch, Rafael; Nagoshi, Emi (Frontiers in Physiology, 2021)
Studies of circadian locomotor rhythms in Drosophila melanogaster gave evidence to the preceding theoretical predictions on circadian rhythms. The molecular oscillator in flies, as in virtually all organisms, operates using transcriptional-translational feedback loops together with intricate post-transcriptional processes. Approximately150 pacemaker neurons, each equipped with a molecular oscillator, form a circuit that functions as the central pacemaker for locomotor rhythms. Input and output pathways to and from the pacemaker circuit are dissected to the level of individual neurons. Pacemaker neurons consist of functionally diverse subclasses, including those designated as the Morning/Master (M)-oscillator essential for driving free-running locomotor rhythms in constant darkness and the Evening (E)-oscillator that drives evening activity. However, accumulating evidence challenges this dual-oscillator model for the circadian circuit organization and propose the view that multiple oscillators are coordinated through network interactions. Here we attempt to provide further evidence to the revised model of the circadian network. We demonstrate that the disruption of molecular clocks or neural output of the M-oscillator during adulthood dampens free-running behavior surprisingly slowly, whereas the disruption of both functions results in an immediate arrhythmia. Therefore, clocks and neural communication of the M-oscillator act additively to sustain rhythmic locomotor output. This phenomenon also suggests that M-oscillator can be a pacemaker or a downstream path that passively receives rhythmic inputs from another pacemaker and convey output signals. Our results support the distributed network model and highlight the remarkable resilience of the Drosophila circadian pacemaker circuit, which can alter its topology to maintain locomotor rhythms.